2005
DOI: 10.1099/ijs.0.63249-0
|View full text |Cite
|
Sign up to set email alerts
|

Polyphasic study of wine Lactobacillus strains: taxonomic implications

Abstract: One hundred and seventy-eight lactobacilli isolated from wine were characterized by a polyphasic approach. Strains were phenotypically identified at genus and species level by classical tests including the analysis of cell morphology, homo/heterofermentative character, sugar fermentation patterns, growth at different temperatures and the optical nature of the isomer of lactic acid produced from glucose. Molecular techniques such as random amplification of polymorphic DNA (RAPD), amplified 16S rDNA restriction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
71
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 61 publications
2
71
1
2
Order By: Relevance
“…UCC125-128 (Accession no: EU074850), isolated in this study shared 98% sequence similarity with an un-speciated Lactobacillus sp. 88 37 . They were also found to have 97% sequence similarity with Lactobacillus mali 2 .…”
Section: Species Identification Of Bacteriocin-producing Labmentioning
confidence: 99%
“…UCC125-128 (Accession no: EU074850), isolated in this study shared 98% sequence similarity with an un-speciated Lactobacillus sp. 88 37 . They were also found to have 97% sequence similarity with Lactobacillus mali 2 .…”
Section: Species Identification Of Bacteriocin-producing Labmentioning
confidence: 99%
“…nov. is proposed. The type strain is 203 T (5CECT 7310 T 5DSM 19674 T ).Eighteen different species of the genus Lactobacillus have been reported to be involved in the winemaking process (Chalfan et al, 1977;Costello et al, 1983;Davis et al, 1986;Lafon-Lafourcade, 1983;Lafon-Lafourcade et al, 1983;Maret & Sozzi, 1977, 1979 Ribéreau-Gayon et al, 2000b;Rodas et al, 2005;Wibowo et al, 1985). In recent years, three of them have been described as novel species, namely Lactobacillus kunkeei (Edwards et al, 1998), Lactobacillus nagelii (Edwards et al, 2000) and Lactobacillus vini (Rodas et al, 2006).…”
mentioning
confidence: 99%
“…In recent years, three of them have been described as novel species, namely Lactobacillus kunkeei (Edwards et al, 1998), Lactobacillus nagelii (Edwards et al, 2000) and Lactobacillus vini (Rodas et al, 2006). Wine lactobacilli are sometimes considered as spoilage organisms since they can produce acetic acid and/ or off-flavours Wibowo et al, 1985;Fleet, 1993;Sponholz, 1993) and biogenic amines (Lonvaud Funel, 2001; Ribéreau-Gayon et al, 2000a;Landete et al, 2005).In an earlier study, Rodas et al (2005) carried out an extensive polyphasic analysis using genotypic and phenotypic methods to characterize 170 lactobacilli isolated from musts and wines. The dendrogram built by comparing the results obtained from the different techniques showed that strain 203 T did not cluster with any of the reference species of the genus Lactobacillus.…”
mentioning
confidence: 99%
“…16S-ARDRA (amplified rDNA restriction analysis), ISR (internal spacer region) analysis, RAPD (randomly amplified polymorphic DNA) analysis and ribotyping were used to characterize this strain genotypically, as described previously (Rodas et al, 2003(Rodas et al, , 2005Chenoll et al, 2006). Strain IMCC1736 T could be differentiated from the reference strains by RAPD and ribotyping profiles, but not by the other techniques based on ribosomal gene analysis.…”
mentioning
confidence: 99%
“…On the basis of these results, a novel species of the genus Lactobacillus is proposed. The almost-complete 16S rRNA gene sequence of strain IMCC1736 T (1528 bp) was obtained using the protocol described by Rodas et al (2005) and, together with sequences from its nearest relatives, including the recently described 'L. uvarum ' (Mañes-Lázaro et al, 2008), was subjected to phylogenetic analysis.…”
mentioning
confidence: 99%